2020
DOI: 10.1186/s42826-019-0035-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the metabolic effects of treadmill and wheel running exercise in mouse model

Abstract: Aerobic exercise is well known to have a positive impact on body composition, muscle strength, and oxidative capacity. In animal model, both treadmill and wheel running exercise modalities have become more popular, in order to study physiological adaptation associated with aerobic exercise. However, few studies have compared physiological adaptations in response to either treadmill exercise (TE), or voluntary wheel running exercise (WE). We therefore compared each exercise intervention on body composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 18 publications
(17 reference statements)
5
27
3
Order By: Relevance
“…In contrast to previous studies (Chen et al, 2014), there was no improvement in grip strength parameters in either the FUC or FUC+EX groups (Figure 1c,d). Consistent with previous studies (Kim et al, 2020), treadmill exercise did not significantly improve grip strength in the VEH experimental groups (Figure 1c,d).…”
Section: Resultssupporting
confidence: 92%
“…In contrast to previous studies (Chen et al, 2014), there was no improvement in grip strength parameters in either the FUC or FUC+EX groups (Figure 1c,d). Consistent with previous studies (Kim et al, 2020), treadmill exercise did not significantly improve grip strength in the VEH experimental groups (Figure 1c,d).…”
Section: Resultssupporting
confidence: 92%
“…Consistent with recent data by Kim et al., 2020, we found a trend toward increased weight of G in response to VWR. However, inconsistently, this tendency was also (even more strongly) observed in T, a muscle where Kim et al saw no effect.…”
Section: Discussionsupporting
confidence: 93%
“…Since weight gain was not significantly different, it is likely that food consumption was higher in the VWR group, which might also have affected the results. This assumption is supported by recent data by Kim et al., 2020, who also compared the effects of FTR and VWR: The authors found increased food intake in exercising, particularly in VWR, mice. Interestingly, however, whereas Kim et al reported decreased gains in body weight in exercising, particularly in VWR, mice, in our study, weight gain in FTR (Schmitt et al., 2018) and VWR (this study) mice was not different from that observed in sedentary controls.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Following weaning at 5 weeks of age, animals were randomly assigned to individual cages under one of four groups ( n = 8 per group): wild-type (WT) C57BL/6 mice with access to a free running wheel (VWR) or a locked wheel (SED) and Muc2 −/− mice with access to a free wheel (MVWR) or a locked wheel (MSED). We chose wheel running as a model of PA over forced exercise, as mice voluntarily run higher total distances on free wheels than when forced on a treadmill ( 73 ). Forced exercise can also cause significant stress in rodents ( 74 ) and has been shown to exacerbate colitis severity in C57BL/6 mice ( 9 ).…”
Section: Methodsmentioning
confidence: 99%